(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
The rapid growth of cryptocurrencies has introduced significant changes to the global financial landscape, raising important questions about their implications for financial stability. This study examines the level of cryptocurrency adoption among individuals and analyses its impact on financial stability, with particular emphasis on associated risks, opportunities, and policy responses. Using a descriptive and analytical research design, primary data was collected from 120 respondents in Pune city through a structured questionnaire, supported by secondary data from academic literature, regulatory reports, and policy documents. The findings reveal moderate awareness and selective adoption of cryptocurrencies, with investment emerging as the primary motive for usage. While respondents acknowledged opportunities such as faster transactions, financial innovation, and potential financial inclusion, concerns regarding price volatility, cybersecurity threats, and regulatory uncertainty remained prominent. The study also highlights strong public support for government regulation to enhance trust and safeguard the financial system. Overall, the research underscores the need for balanced regulatory frameworks that encourage innovation while addressing risks to ensure the stable integration of cryptocurrencies into the formal financial ecosystem.